The effectiveness of the promotional tools practice by Netherlands Maritime Institute of Technology / Nor Azila Zolkafli - Zolkafli, Nor Azila (Faculty of Business and Management, 2011)
The area of study covers the important of marketing mix and promotional tools practices toward increasing the NMIT student intake by creating awareness among the potential student. In this research case study, I cover on defining the marketing, marketing mix concept, the promotional tools practices by the organization and the important of maritime industry in Malaysia. The main important is to determine is the promotional tools practice by the NMIT either is effective enough in order to achieve the target number of students registered. For the company practices, this study will analyze the implemented promotional tools result in order to determine which of the promotional tools is most effective in creating awareness and promoting the NMIT. This also include the comparison of the fees among the competitors, the list of competitors existed in Malaysia and the list of busiest port in the world to influence the youngster to enter the maritime industry.